Applying Cognitive Linguistics to teaching English prepositions in the EFL classroom - Wijaya, David; Ong, Gabriella (Universitas Pendidikan Indonesia, 2018)
This paper reports on a quasi-experimental study investigating the effect of cognitive linguistics-grounded instruction on learning the prepositions in, on, and at, which are known to pose tremendous difficulty to English language learners due to their language-specific features and polysemous nature. The participants (N = 44) were adolescent learners at a school in Indonesia. They were assigned into the cognitive group and the rule group. The cognitive group was presented with pictorial representations of the prepositions and cognitive tools used to motivate non-spatial uses, while the rule group was provided with rules. Participants’ performance on the three uses (i.e. spatial, temporal and abstract) was measured with pre-, post-, and delayed post-tests in a form of gap filling. The study yielded mixed results. The findings demonstrate that the cognitive group outperformed the rule group in the overall immediate and delayed post-tests. The cognitive group improved significantly in the immediate post-test; however, the positive effect did not last until the delayed post-test. On the other hand, the rule group gained a little in the immediate post-test, but the group’s performance decreased significantly in the delayed post-test. Although there was no indication of long-term effects of the cognitive instruction, the results still indicate a value of applying cognitive linguistics to teaching the prepositions, and thus lend support to the applicability of cognitive linguistic theory in second language instruction.